2018
DOI: 10.1002/ange.201808178
|View full text |Cite
|
Sign up to set email alerts
|

Undecabenzo[7]superhelicene: A Helical Nanographene Ribbon as a Circularly Polarized Luminescence Emitter

Abstract: We report the synthesis and characterization of an enantiopure superhelicene nanographene constituted by two saddleshaped and one planar hexabenzocoronene (HBC) units arranged in a helicoidal shape. This is, to the best of our knowledge, the first undecabenzo[7]carbohelicene, i.e., the first fully π-extended [7]helicene. Racemic resolution allowed its chiroptical properties analysis revealing dissymmetry factors in the range of 2×10-3 both in the absorption and in the emission measurements. Remarkably, nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…Another research direction in helicene chemistry is the lateral extension of π-conjugated systems. 9 − 20 With more extensive conjugation, π-extended helicenes can be regarded as nanosolenoids and are predicted to possess intriguing electronic, magnetic, and spin properties. 21 23 In addition, their fascinating chiroptical features, such as circular dichroism (CD) and circularly polarized luminescence (CPL), have been intensively studied and are valuable for circularly polarized organic light-emitting diodes and bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research direction in helicene chemistry is the lateral extension of π-conjugated systems. 9 − 20 With more extensive conjugation, π-extended helicenes can be regarded as nanosolenoids and are predicted to possess intriguing electronic, magnetic, and spin properties. 21 23 In addition, their fascinating chiroptical features, such as circular dichroism (CD) and circularly polarized luminescence (CPL), have been intensively studied and are valuable for circularly polarized organic light-emitting diodes and bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of such π-extended helicenes as CPL emitters has not been well explored. For example, an excellent Φ (>0.80) was achieved by a HBC-fused oxa[7]superhelicene, but its g lum was only 2 × 10 –4 ( Scheme 1 A); 10 , 29 a moderate g lum (2 × 10 –3 ) and a low Φ (0.098) were reported for another HBC-based undecabenzo[7]superhelicene ( Scheme 1 B); 9 , 23 and in a series of PDI-embedding double [8]helicenes, only moderate values of g lum (up to 2 × 10 –3 ) and Φ (up to 0.30) were observed ( Scheme 1 C). 19 After the initial submission of this manuscript, Santoro, Schuster, Nuckolls et al reported amplified CD signals by extending the helical length, but did not study the CPL performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, conformationally stable π-extended [n]-helicenes (with n ≥ 5) have lately received increased attention. [3] Such helicenes commonly consist of large planar segments, that is, the "πextension" and one or more twisted parts, that is, the "helicene".…”
mentioning
confidence: 99%
“…Such a versatility is rather uncommon and renders our superhelicenes to stand out from the vast majority of published π-extended helicenes. [3] In the original synthesis of oxa- [7]-superhelicene, [13] we started from a diphenyl ether precursor. In the final step of the synthesis, it was necessary not only to close the hexaarylbenzenes, but also the furan ring to obtain the extended helicene.…”
mentioning
confidence: 99%
“…In recent years, enlarging the π-conjugated plane of helicenes and fusing multiple helicenes into a PAH core have led to a variety of elegant molecules that extend chiroptical responses to the visible spectral range. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Nevertheless, the absorption dissymmetry factors (gabs) are generally in the range of 10 -4 ~ 10 -3 , 30 with only very few compounds showing gabs on the order of 10 -2 . [12][13][14][15][16][17] Therefore, it is highly demanding to develop novel helicene materials with high gabs in the visible range for future chiral optoelectronic applications.…”
Section: Main Textmentioning
confidence: 99%